Influence of a recessed step at the throat section of a supersonic nozzle. (20th February 2018) - Zocca, M.; Spinelli, A.; Cozzi, F.; Guardone, A.
ABSTRACT: The geometry of a planar converging-diverging nozzle operating with dry air in dilute gas conditions is modified by the introduction of a small recessed step at the throat section. Pressure measurements along the nozzle axis, schlieren visualisations and numerical simulations are performed to investigate the influence of the recessed step on the supersonic flow-field. In the experiments, the height of the recessed step is 0.1 mm and the nozzle height at the throat is 10 mm. Numerical simulations examine also 0.05 mm and 0.2 mm step heights. From the numerical simulations, the flow Mach number at the step location is 1.04 and the Reynolds number computed using the sonic conditions and the throat half-height is Re = 3.73 × 10 5 . A perturbation wave pattern originates from the step, which results in a perturbation of the measured pressure profile close to the throat section. In the diverging portion, sufficiently far from the throat section, the pressure profile of the recessed-step nozzle matches the one measured in the clean configuration.